Performance and Emission Assessment of Tree-Based Biofuel Additives in Compression Ignition Engines: A Review - Ilmi , Ilmi; Sitorus, Tulus Burhanuddin; Siagian, Parulian; Sihombing, Roland (Pt. Anagata Sembagi Education, 2026)
This study reviews the performance and emissions of compression ignition (CI) engines using Calophyllum inophyllum (CIME/tamanu)-based biofuel additives through a narrative review of the latest international literature. Inclusion criteria encompassed CI engine test studies reporting efficiency metrics (BTE, BSFC) and key emissions (CO, HC, NOx, smoke/PM) for CIME blends (B10–B100) both without and with additive/mitigation strategies. In general, compared to diesel, CIME reduced CO, HC, and smoke/PM, with a trade-off increase in NOx. The addition of oxygenated additives (e.g., n-pentanol, dimethyl carbonate) and ignition improvers (e.g., DTBP) tends to improve combustion quality, reduce BSFC, and suppress CO/HC; while the application of approximately 10% EGR effectively reduces NOx with a moderate penalty on HC/CO/smoke. Nano-additives (graphene/MWCNT) show potential for increasing BTE and reducing smoke, but present issues of dispersion stability and safety/environment. The most balanced performance generally occurs at low–medium blends (≈B10–B20) combined with oxygenated additives and EGR-based NOx control, accompanied by proper injection calibration. From a sustainability perspective, C. inophyllum—as a non-food source with high FFA pretreatment requirements—has the potential to support transportation decarbonization, although industrial-scale success depends on supply chains, policies, and LCA/TEA results. Further studies are recommended on real-world test cycles, long-term durability, aftertreatment compatibility, and comprehensive environmental assessment.